Manifestações neurológicas em pacientes com doença de Crohn e retocolite ulcerativa - Oliveira, Gisele Ramos de (2008)
Several neurological disorders have been described in inflammatory bowel disease (IBD) patients, but their exact prevalence is unknown. We prospectively studied the prevalence and incidence of neurological disorders in a cohort of 82 patients with IBD (protocol 1) and the presence and severity of tremor in patients with IBD or healthy volunteers (Protocol 2). Patients from protocol 1 were evaluated at the IBD Clinic from the Hospital Walter Cantídio for at least one year, with complete periodic neurological evaluations. The second protocol consisted in quantifying the amount of tremor in Archimedes spirals from patients with Crohn´s disease (CD, N=31), ulcerative colitis (UC, N=63) and healthy volunteers (N=41) by a neurologist specialized in movement disorders (Dr. Elan Louis, Columbia University, New York City). Sensory or sensorimotor large-fiber polyneuropathy was observed in 16.1% of the patients with CD and 19.6% of the patients with UC. Neuropathy was usually mild, predominantly distal, symmetric, and axonal. Carpal tunnel syndrome was more commonly observed in women with UC. Sensory complaints without electrodiagnostic (EMG) abnormalities suggestive of small fiber neuropathy or subclinical myelopathy were observed in 29% of the patients with CD and 11.8% of the patients with UC. After excluding other etiological or contributory factors for the development of neuropathy, still 13.4% of the IBD patients had large or small fiber neuropathy (7.3% had large-fiber polyneuropathy). Non-debilitating headache was the most common neurological complaint, 3 patients had strokes, 5 were diagnosed with epilepsy and one had transient chorea. Patients with IBD had lower scores of tremor in the Archimedes spiral assessment due to decreased caffeine intake. In patients with CD, there was a significant correlation between tremor grade, use of medications with effect on the central nervous system, use and amount of caffeine intake and presence of other neurological conditions. In patients with UC, there was only a significant correlation between tremor grade, age and use and the amount of caffeine intake prior to the evaluation. In summary, patients with CD and UC exhibit a wide range of neurological manifestations that are frequently neglected clinically.